The contribution of mentors to support beginning teachers: The case of primary schools - Dagnew, Asrat (International Journal of Psychosocial Rehabilitation, 2024)
The purpose of this study was to assess the contribution and responsibilities of mentors insupporting beginning teachers in primary schools. Its’ internal consistency was 0.85.Mentors,beginning teacher, and principal respondents were selected randomly to fill out the questionnaireproperly. Data gathered from 33 mentors, 63 beginning teachers, and 14 principals were analyzedand interpreted. Furthermore, portfolio of beginning teachers and information obtained throughobservation were incorporated. The findings of the study indicated that mentors did not supportfresh teachers effectively, although mentors seem good in knowing their contribution andresponsibilities. Absence of training, shortage of time and logistic, lack of interest, little number ofexperienced teachers in remote schools and absence of planned regular meeting were identified ascrucial factors that affect mentoring relationship. The relationship between mentors and beginningteachers was found good. Accommodating students’ difference, in- effective evaluation, andabsence of well developed content knowledge were identified as problem facing the noviceteachers. Providing mentoring training, encouraging experienced teachers to retain in the remoteschools for longer years, appropriate support by district expert and sharing experience fromexperienced teachers are some of the possible solutions.